ChemInform Abstract: The Evolution of Immobilized Reagents and Their Application in Flow Chemistry for the Synthesis of Natural Products and Pharmaceutical Compounds. Issue 17 (4th April 2013) - Myers, Rebecca M.; Roper, Kimberley A.; Baxendale, Ian R.; Ley, Steven V.
Abstract Review: 77 refs.